Amazing Volcanoes. (Dockland, Victoria, Oxford University Press, 2019)
Amazing Volcanoes is an informative and visually engaging non-fiction reader that introduces children to the powerful forces of nature behind volcanic eruptions. It covers what volcanoes are, how they form, different types of volcanoes, famous eruptions in history, and the role of volcanoes in shaping the Earth. The text supports inquiry-based learning and encourages curiosity about Earth sciences, making it ideal for independent reading or classroom use in science units.
Amazing Volcanoes is an informative and accessible non-fiction book written by Pamela Rushby for young readers. The book introduces the science behind volcanoes, exploring how they form, the different types that exist, and the impact they have on people and the environment. With engaging visuals and straightforward explanations, it encourages scientific curiosity and supports foundational knowledge in earth sciences. Designed for primary school students, the book is ideal for use in classrooms, libraries, and at home. It can support independent reading or serve as a valuable supplement to science units on natural disasters, geology, and Earth's structure.
Keywords: text